A novel shear strength model for partially encased composite (PEC) beams based on strain compatibility. (15th September 2022) - Xue, Yicong; Hao, Ning; Yang, Yong; Yu, Yunlong
Highlights: The existing shear equations for PEC beams are critically reviewed. The anti-shear mechanisms (composite truss and steel web) are re-defined based on test observations. The shear contributions of composite truss and steel web are evaluated using strain compatibility. The proposed shear strength model improves the accuracy compared with existing methods. Abstract: Steel and concrete composite beam has been widely applied in large-span or heavily-loaded structures; however, the large shear force at the beam supports may cause web crippling or local damage. To address this problem, partially encased composite (PEC) beams, in which steel web is encased in concrete or reinforced concrete, are proposed to enhance the load-carrying capacity, anti-crippling, and anti-fire performances. In engineering practice, the vertical shear usually governs the final failure at intermediate supports; hence, accurate shear strength prediction is essential for PEC beams in practical design. Although some existing test results and shear equations exist for shear-critical PEC beams, the shear mechanism is still unclear because two shear force transferring mechanisms are coupled by the structural steel and web concrete. Therefore, it is essential to explore the contributions of the different mechanisms and how they work together as a composite structure. In this paper, the shear strength equations in current design codes and the shear strength models proposed by other researchers were reviewed and evaluated using a database consisted of the existing test results of 27 large-scale PEC beams. After identifying the shortcomings of these equations and models, this paper proposed a novel shear strength model, in which the shear contributions of the structural steel and web concrete were determined by von Mises yielding law and composite truss analogy, and the interaction between these two parts was evaluated by the strain compatibility. Finally, a comparison with the database was reported to verify the applicability of the proposed model. The results indicated that the proposed model could predict the shear strength of PEC beams with sufficient accuracy, and the strain compatibility could reasonably decouple the shear contributions of different anti-shear mechanisms.